2018
DOI: 10.31436/iiumej.v19i1.826
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Rheology of Non-Newtonian Properties of Blood

Abstract: Human blood is composed of red cells, white blood cells, and platelets in a fluid called plasma that contains organic and mineral salts and protein. The rheological characteristics of blood are determined by the properties of these combinations and their interaction with each other. The plasma is essentially a Newtonian fluid, but the blood as a whole behaves as a non-Newtonian fluid showing all signs of non-Newtonian rheology including deformation rate dependency, viscoelasticity, yield stress, and thixotropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Hemorheology refers to the study of blood flow and its related properties, including viscosity, deformability of blood cells (such as RBCs), and the behavior of blood under various conditions. [85] In diabetes, micro-angiopathic complications often arise due to alterations in hemorheological parameters, impacting blood flow and microcirculation in small blood vessels. [86] Diabetes can lead to increased blood viscosity, primarily due to higher levels of plasma proteins, such as fibrinogen and globulins, as well as elevated levels of lipids and hyperglycemia-induced changes in blood components.…”
Section: Hemorheological Changes On Micro-angiopathic Complications I...mentioning
confidence: 99%
“…Hemorheology refers to the study of blood flow and its related properties, including viscosity, deformability of blood cells (such as RBCs), and the behavior of blood under various conditions. [85] In diabetes, micro-angiopathic complications often arise due to alterations in hemorheological parameters, impacting blood flow and microcirculation in small blood vessels. [86] Diabetes can lead to increased blood viscosity, primarily due to higher levels of plasma proteins, such as fibrinogen and globulins, as well as elevated levels of lipids and hyperglycemia-induced changes in blood components.…”
Section: Hemorheological Changes On Micro-angiopathic Complications I...mentioning
confidence: 99%
“…This includes questions of belief in the Islamic religion. According to the rules or experts, Tauhid Science is defined as "a science that discusses all religious beliefs using convincing arguments" (Fatahian, Kordani, and Fatahian 2018). Tawhid encourages humans to master and utilize the universe because it has been subjugated to humans (QS.…”
Section: The Relationship Between Tawhid and Sciencementioning
confidence: 99%
“…It was previously shown that the non-Newtonian nature of blood acts as a regulating factor to reduce the flow resistance and wall shear stress thereby considering shear thinning to have the most significant role in facilitating blood flow through stenotic vessels (Shukla et al, 1980). Moreover, blood is usually considered as a predominantly shear thinning fluid, especially under steady flow conditions (Fatahian et al, 2018). Thus, this property seems to have the most important non-Newtonian impact (Sochi, 2013).…”
Section: Modeling Of the Capillary Blood Flowmentioning
confidence: 99%